DISTRACTION (GANGGUAN) DALAM PEMBELAJARAN ONLINE - Lismawani Lismawani; Shadiqin Shadiqin (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Changes in the teaching and learning process, which initially took place face-to-face learning are now carried out by online learning, experienced several obstacles or disturbances ranging from inadequate internet quotas, unstable networks to lack of students' understanding of the material presented by the teacher. Online learning is one of the ways recommended by the government to maximize the quality of learning during the Covid-19 pandemic. The results of the study show that the disruption in online learning, among others, is that first, students do not focus on learning due to boredom and boredom in students so that the teacher must implement strategies that make the learning atmosphere happier. Second, there are inadequate online learning facilities because not all students have online learning support devices, and there are also areas that are not covered by the internet. Third, there is no readiness of teachers and parents of students for online learning, where there are still teachers who do not have the competence to teach online and also parents have their own activities, so they cannot accompany students when online learning takes place.